Emergency Data Transmission for Disaster Planning in MANETs - Mary, M.P. Virgin (International Journal of Computer Sciences and Engineering, 2025)
Wireless Ad-hoc Networks encompass variety of nodes that communicate with one another over a wireless channel that have numerous forms of networks, device networks, ad-hoc networks, and so on. The most drawback in these channels is expounded to security as a result of the secure communication, a very important side of any networking setting, is associate particularly vital challenge in spontaneous networks. A reliable system for such message exchanges is considered to be a particular strength for such organizations. Information security is a more general concern for officers of the armed forces and armed forces personnel is in constant pursuit of better procedures to ensure data protection and integrity. Privacy is needed in Ad-hoc networks. A secured on demand position based private routing algorithm is proposed for communication and which provides a security in Mobile Ad-hoc Network. This proposed is used for security to prevent message hacking information from internal & external attackers